PELABELAN GRACEFUL SATU MODULO PADA BEBERAPA GRAF EULE - Isa Isa; Lucia Ratnasari (MATEMATIKA FSM, UNDIP, 2014)
ABSTRACT. A graph with edges is said to be one modulo graceful graph () if there is a injective function from vertex set of graph to in such a way that induces a function from edge set of graph to defined as is bijective. In this Last Project, the following Euler graphs : n-polygonal snakes, and under certain conditions which admit one modulo graceful labeling () are learned.